2006
DOI: 10.1002/jsfa.2510
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of acetic acid and formic acid in breakfast cereals

Abstract: Breakfast cereals are usually manufactured by extrusion followed by drying and toasting steps in which thermal treatments are applied. In addition, owing to the low water activity and the content in cereals of proteins and carbohydrates, precursors of the Maillard reaction, this reaction and degradation of sugars are favoured during processing. Acetic and formic acids have been identified as final products of Maillard reaction (MR) and sugar caramelisation. Acetic and formic acid contents have been determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Nevertheless, maltose could trigger to produce formic, acetate, lactic acid, propanoic acid and citric acid, and damage the ester bond of chlorogenic acid for the formation of quinic, ferulic, cinnamic, and caffeic acids after heating. [15][16][17] Moreover, our data showed that maltose directly induced a rapid and burst increase of intermediates in the reaction. However, application of Lys has demonstrated an obviously limited effect on hydroxymethylfurfural and other intermediary products (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, maltose could trigger to produce formic, acetate, lactic acid, propanoic acid and citric acid, and damage the ester bond of chlorogenic acid for the formation of quinic, ferulic, cinnamic, and caffeic acids after heating. [15][16][17] Moreover, our data showed that maltose directly induced a rapid and burst increase of intermediates in the reaction. However, application of Lys has demonstrated an obviously limited effect on hydroxymethylfurfural and other intermediary products (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Compared to the control, the combined treatments of maltose with Lys were obviously effective in promoting release of new volatile profiles containing aldehydes (6,33,79,88), phenols (19,32,50,54,85), furans (13,26,58), pyrazines (15,40,41,42,44,45,56, 60, 62, 67), alcohols (23), pyridine (5,30,49), alkene (17,36), pyrimidine (21), ketones (34,48,66,71,76,84), amine (39, 53, 61, 86, 87), pyrrole (46, 47, 69), imidazole (68), ethers (80) and others (37, 51, 59, 70, 72, 75, 77, 78, and 83). However, maltose-, Lys-and combined-treatment led to a decreased or not significantly (P > 0.05) increased effect on certain volatiles such as aldehydes (1,7,18,20,31,55, 64 and 74), phenols (35,73), furans (9, 57), pyrazines (10, 43), alcohols (8,12), and amines (82).…”
Section: Spme-gc-ms Analysismentioning
confidence: 99%
“…Rufian-Henares et al, [19] who demonstrated that the monosaccharide degradation products were 1-deoxyglucosone and 3-deoxyglucosone (compounds that were also generated from the MR),…”
Section: Changes In Phmentioning
confidence: 98%
“…Nevertheless, the lowest pH value was found in the glucose control system. This phenomenon may be due to the production of formic and acetic acids from glucose, which is partly degraded to these compounds when it is heated at high pH either in the presence of protein or not (Rufian-Henares, Delgado-Andrade, & Morales, 2006).…”
Section: Changes Of Phmentioning
confidence: 98%